Construction and Restoration Strategies of Green Infrastructure Network in Mountainous Counties Based on Multi-Source Data: A Case Study of Wanzhou District, Chongqing - Wang Ziming; Lyu Liang; Wang Feng (Redai dili, 2024)
The conflict between ecological protection and town development is particularly pronounced in mountainous towns with fragile ecological environments and constrained construction conditions. Cross-scale Green Infrastructure (GI) is characterized by a balance between ecological protection and human needs. The establishment of a county-level GI network can provide a shared basic framework for the development and biological conservation of mountainous towns. The Wanzhou District of Chongqing has the typical characteristics of a southwestern mountain town with ecological problems such as habitat fragmentation and reduced disturbance resistance. This study was based on the biological flow process, guided by geometric morphology, circuit, and graph theory, and it followed the logic of "hubs, links, and pinch points". First, the morphological spatial pattern analysis method was applied to identify the GI network hubs, and their importance was classified according to the current-flow betweenness centrality index. Next, an ecological resistance surface was established based on multi-source data, and the minimum cumulative resistance model was applied to identify the links. It also calculated their importance and ranked them based on the average resistance, path length, and average value of the connected hubs. Subsequently, the current-flow density distribution was analyzed, and ecological pinch points were extracted in conjunction with the links. According to the results, the GI network of Wanzhou District contains 42 hubs with an area of 996.35 km2, accounting for 28.83% of the total study area. The hubs were generally dense in the east and sparse in the west, forming a pattern of "one screen, three belts, and scattered distribution." Among them, the GI network hubs formed by the Fangdou-Qiyao Mountain group and the Yangtze River and its coastal green areas are of the greatest importance, followed by the Tiefeng Mountain, Dengfeng Reservoir, and the central-eastern forest areas, whereas the small patches scattered in the central southwest-northeast oriented valleys are of the least importance. Additionally, 80 links were identified with a total length of 292.97 km, with long paths and low importance in the eastern region and short paths and high importance in the western region. Furthermore, 142 ecological pinch points were extracted, accounting for 9.60% of the corridor length dominated by land-use types of farmlands (55.89%) and woodlands (35.71%); pinch points were mainly concentrated in the east, which is the key area in guaranteeing the ecological stability of the county GI network. Finally, this study proposes zoning, grading, and precise protection and restoration strategies based on the relative importance of hubs and links and the land-use types of ecological pinch-point areas. These strategies provide a scientific basis for decision-making to coordinate the conservation and development needs of mountain towns.